Pengaruh Profitabilitas, Intensitas Aset Tetap, dan Leverage Terhadap Penghindaran Pajak Pada Perusahaan Sektor Manufaktur yang Terdaftar di BEI Tahun 2017-2019 - Oky Afriyan; Nurmala Nurmala; Lihan Rini Puspo Wijaya (Politeknik Negeri Lampung, 2022)
The purpose of this study was to examine the effects of profitability, intensity of fixed assets, and leverage on tax avoidance by focusing on manufacturing companies registered in Indonesia Stock Exchange in the period of 2017 – 2019. Tax avoidance was a dependent variable, while profitability, fixed assets, and leverage were independent variables. The sampling method used was purposive sampling with a sample of 54 companies with the observation period of three years in a row to produce a total of 162 samples. The analysis technique used in this research was multiple linear regression analysis. Data were analyzed using SPSS 25. The results of this study indicate that profitability has an effect on tax avoidance; intensity of fixed assets has an effect on tax avoidance, and leverage has an effect on tax avoidance.